Invoking the domain competence principle in India's maritime governance: A case for an Indian Maritime Service. (3rd July 2021) - Vijay, Adarsh; Vidya, R.; Kiran Raghul Raj, S.
ABSTRACT: India's growing role as a maritime powerhouse beckons unprecedented opportunities and challenges. The present mode of maritime governance characterised by the outdated role of generalists, particularly the Indian Administrative Service (IAS), is nothing more than an unfaded representation of a colonial stopgap arrangement with no scientific substance per se. Irrespective of an ideation that took place in 2014, the Indian Maritime Service (IMS) as a technocratic cadre for maritime administration never came to fruition. The commentary builds a rationale for IMS as a non-uniformed branch of specialists in view of the highly technical frontiers of civilian maritime domain, which is left in the hands of generalists. It concludes with the requirement of recalibrating the civil services with sub-specialist credentials to enhance the Indian maritime trajectories.